Functional MPO Polymorphisms and Haplotypes Affect Both Myeloperoxidase Levels and Association with Hypertensive Disorders of Pregnancy - Pereira, Daniela Alves [UNESP]; Luizon, Marcelo Rizzatti [UNESP]; Cavalli, Ricardo Carvalho; Tanus-Santos, Jose Eduardo; Sandrim, Valéria Cristina [UNESP] (MDPI, 2025)
Preeclampsia (PE) shares common pathophysiological mechanisms with cardiovascular diseases, including endothelial dysfunction and exacerbated inflammatory response. Myeloperoxidase (MPO) has been suggested as a biomarker for cardiovascular risk, and its circulating levels are contradictory in PE. Elevated levels of MPO can promote host tissue damage and trigger vascular injury. MPO gene polymorphisms affect circulating MPO levels under different conditions. To date, no studies have investigated whether MPO polymorphisms influence MPO levels in hypertensive disorders of pregnancy. In this study, we examined the impact of two specific MPO polymorphisms-rs2243828 and rs2071409-and their associated haplotypes on MPO levels. We also explored their potential association with gestational hypertension (GH) and preeclampsia (PE). Our study included 136 healthy pregnant women (HP), including 118 with GH and 140 with PE. Genotyping was performed using TaqMan allele discrimination assays, and MPO levels were quantified using an ELISA assay. The TT genotype of the rs2243828 polymorphism was associated with lower MPO concentration in GH, and the CC genotype presented a higher frequency in the GH group than the HP group. The AC+CC rs2071409 polymorphism was associated with lower MPO concentration in GH. We also found that the 'C, C' haplotype was less frequent and was associated with lower MPO concentration in PE. Our findings suggest that both rs2243828 and rs2071409 polymorphisms might contribute to MPO levels in GH and that the haplotype 'C, C' formed by them may protect against PE.